Remanufacturing with material restrictions in monopoly and duopoly. (20th April 2022) - Zhou, Tao; Li, Kai; Yang, Shan-Lin
In this paper, we study firms' pricing and competitive strategies. We discuss a monopolistic scenario with an original supplier (OS) and a duopolistic scenario with an additional independent supplier (IS). Moreover, we investigate the effects of manufacturing cost, remanufacturing cost, customer discount factor, acquisition rate and the entry of a competitor on OS's strategies. Our results show that, in monopoly, the OS's remanufacturing possibility does not always increase in customer discount factor. Moreover, a lower manufacturing cost promotes complementary relationships between new and remanufactured products. In duopoly, a lower manufacturing cost reduces the remanufacturing possibility of the IS. Furthermore, raising the price of a remanufactured product may not reduce the consumer demand. The proposed model can be applied to many industries where the managers have the full awareness of extended producer responsibility, and they are willing to engage in the project related to remanufacturing. [Submitted: 2 January 2020; Accepted: 6 June 2021]